Nitrous Oxide Emissions Generated in Coffee Cultivation: A Systematic Review. - Quiñones Huatangari, Lenin (2022)
The objective of the research was to provide an overview of soil N2O emissions in coffee cropping systems; summarizing available field data on soil emissions and identifying controlling factors (fertilizer type, precipitation, temperature, altitude). A systematic search of Scopus, Science Direct, Springer, and Scielo for experimental-type studies was conducted from January 2000 to October 2021. Of the seventy manuscripts determined through the search strategy, eight studies met the inclusion criteria. Analysis of the included studies revealed that they were conducted in Ecuador, Costa Rica, and Nicaragua; the rainfall of the fields ranged from 910 mm to 2740 mm per year and the average temperature was 20.3°C. Coffee is planted under agroforestry systems and monocultures; in addition, the most abundant forest species in coffee agroforestry systems are leguminous plants of the Inga and Erytrina genus and 60% of the studies have been developed with the Catuai coffee variety. The pH and humidity of the soil where coffee plantations are developed range from 4.67 to 6.34 and 53.3 to 67.05% respectively. Finally, the fertilizers used are of chemical, organic, and chemical + polymer origin, at fertilization rates ranging from 66 to 400 kg.N.ha-1yr-1 and N2O emissions ranging from 0.2 to 12.8 kg.N.ha-1yr-1. Overall, the present systematic review provides a scientific basis for evaluating N2O emissions generated in coffee crops.